Hybrid Estimator of Kumaraswamy Distribution Parameter - Abdulkadhim Neamah, Irtefaa; G. Mohsin, Muayad (International Journal of Engineering and Technology, 2018)
This study suggest a hybrid estimator to estimate the shape parameter bof the Kumaraswamy distribution. The suggested approach based on consisting between the MED estimator of exponential distribution and the statistical property median ( MED)of Kumaraswamy distribution. The output estimation will called (Hybrid Estimator). So, how are we will know if this estimator is a best? To answer this question, it is necessary to compute the numerical results and then compare them. The results, which will obtain from simulation study, they will give us the decision. To find out which estimator is better, it must run a system of numerical simulation. Then, the results will be compared using a standard tool like MEA Square Error (MSE). We will use Matlab to implement the simulation steps. Finally, the results show that the hybrid method give the best estimated values and near to the proposed values.Â Â